Impact of Nutritional Methods On Physical Performance Parameters - Szafrańska, Katarzyna; Dominiczak, Kinga; Niemirka, Szymon; Janiak, Aleksandra; Grądalski, Łukasz; Kopaczyńska, Adrianna; Dębicki, Filip (Quality in Sport, 2024)
Abstract Introduction: Contemporary nutritional strategies in sports play a crucial role, and it can be argued that, in a certain sense, they are paramount. This research aims to focus on three dietary approaches commonly utilized in various sports disciplines. The high-carbohydrate diet is particularly influential in endurance sports, owing to its properties that enhance muscle performance and efficiency. The core principle of this diet is the provision of large amounts of carbohydrates, providing the basic source of energy, which allows maintaining the level of glycogen in the muscles and liver. In contrast to high-carbohydrate diets, high-protein and ketogenic diets have gained increasing popularity. The high-protein diet is especially recommended for strength and endurance athletes due to its ability to support anabolic processes and facilitate the repair of micro-muscular damage. On the other hand, the ketogenic diet, characterized by elevated fat intake, induces metabolic adaptations such as ketosis, wherein the body shifts from carbohydrate to fat. Aim of study: The aim of this study is to summarize the available knowledge about how diets influence sports indicators such as strength, endurance and ability to regenerate. The metabolism, mechanisms and different methods of diets were described and summarized. Material and methods: The literature available in PubMed, and the Google Scholar database was reviewed using the following keywords: ,,Ketogenic diet”, ,,High carbohydrate diet”, ,,High protein diet”, ,,Diets in sport”